2011
DOI: 10.1091/mbc.e10-08-0665
|View full text |Cite
|
Sign up to set email alerts
|

A Ral GAP complex links PI 3-kinase/Akt signaling to RalA activation in insulin action

Abstract: It is shown that RalA is regulated by a Ral GAP complex (RGC 1/2) in insulin action and links PI 3-kinase signaling to RalA activation. Akt phosphorylates the complex and inhibits its function, resulting in increased RalA activity and glucose uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 55 publications
6
110
1
Order By: Relevance
“…Our results are consistent with older data arguing the existence of Akt-independent actions of PI3K (Gonzalez and McGraw, 2006). Other signaling pathways, such as PI3K-dependent activation of the exocyst complex (Chen et al, 2011) and atypical protein kinase C pathways (Kanzaki et al, 2004;Liu et al, 2010;Sajan et al, 2014a,b) might be activated in adipocytes, but these have not been well appreciated. Particularly in muscle cells, PI3K stimulates Rac1 signaling, and this is required together with Akt to promote GLUT4 translocation and glucose uptake (Chiu et al, 2011;Klip et al, 2014;Sylow et al, 2014;Ueda et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with older data arguing the existence of Akt-independent actions of PI3K (Gonzalez and McGraw, 2006). Other signaling pathways, such as PI3K-dependent activation of the exocyst complex (Chen et al, 2011) and atypical protein kinase C pathways (Kanzaki et al, 2004;Liu et al, 2010;Sajan et al, 2014a,b) might be activated in adipocytes, but these have not been well appreciated. Particularly in muscle cells, PI3K stimulates Rac1 signaling, and this is required together with Akt to promote GLUT4 translocation and glucose uptake (Chiu et al, 2011;Klip et al, 2014;Sylow et al, 2014;Ueda et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, a downstream target of Akt, AS160, is mobilized to the plasma membrane and regulates GLUT4 vesicle exocytosis (Tan et al, 2012). Therefore, it is conceivable that locally activated Akt might recruit AS160 and its downstream Rab proteins, as well as the exocyst complex (Chen et al, 2011), to control the spatial release of GLUT4 into the plasma membrane. Of note, data presented here support the idea that there is a local permanence of activated Akt effectors, such as AS160, and its targets, such as Rab10 and Rab13, which mediate vesicle tethering, docking and fusion at the plasma membrane (Chen et al, 2012;Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of the exocytic vesicle by the exocyst is mediated by the Rab GTPase proteins, Sec4 in yeast (Guo et al, 1999;Zajac et al, 2005) or Rab11 in metazoans (Novick & Guo, 2002;Novick et al, 2006). In mammalian cells, assembly of this complex is controlled by RalA and RalB (Chen et al, 2011a;Chen et al, 2007;Chen et al, 2011b).…”
Section: The Molecular Machinery For Exocytosismentioning
confidence: 99%
“…During insulin stimulated GLUT4 vesicle transport, phosphorylation of the RalGAP complex by protein kinase Akt2 (downstream of PI3-Kinase) relieves its inhibitory effect on RalA activity, and thereby increases GLUT4 exocytosis at the plasma membrane (Chen, et al, 2011b;. Intriguingly, phosphorylated RalGAP complex was shown to be capable of binding RalA in vitro, and the authors suggested that in cells this phosphorylation may act through sequestering RalGAP in the cytoplasm, away from site of RalA action (X. W. Chen, et al, 2011b). Once activated, GTP-bound RalA protein interacts with Sec5 protein to assemble vesicular and plasma membrane subunits of the exocyst complex.…”
Section: Phospho-regulation Of Small Gtpases Their Effectors and Regmentioning
confidence: 99%